Impact Analysis of New Shield Tunnel Under-passing Construction on Existing Railways - XIAO Fei (Chengshi guidao jiaotong yanjiu)
［Objective］The construction of new shield tunnels under-passing existing railway can cause deformation of the former railway subgrade. To ensure the stability and safety of the existing railway, appropriate reinforcement measures must be adopted. ［Method］The Shanghai Airport Connection Line under-passing Lijiatang-Shenzhuang Railway project is analyzed as a study case, which adopts a reinforcement scheme involving ′portal isolation piles+ground grouting′. Numerical simulation results and on-site monitoring data are used to assess the impact of shield tunnel under-passing construction on the existing railway, and to evaluate the effectiveness of the ′portal isolation piles+ground grouting′ reinforcement scheme. ［Result & Conclusion］The shield tunnel under-passing construction may cause significant settlement of the existing railway subgrade, while the ′portal isolation piles+ground grouting′ reinforcement scheme effectively controls the above-mentioned railway subgrade deformation. According to numerical simulation results, the maximum settlement of existing railway subgrade decreases by 67% after reinforcement, and the convergence deformation on tunnel upper part decreases by approximately 41%. All deformations are within the limits specified by the relevant standards. On-site measurements confirm that the cumulative deformation of existing railway track and subgrade caused by the shield construction meets the regulatory requirements. However, due to the impact of shield tunneling, larger deformation fluctuations are observed in existing railway subgrade and track on one side of the shield tunneling.